Coupling Kinetic Modelling with SAOS and LAOS Rheology of Poly(n‐butyl acrylate). Issue 12 (23rd December 2021) - Grotian genannt Klages, Hannah; Ermis, Nihal; Luinstra, Gerrit Albert; Zentel, Kristina Maria
Abstract: A kinetic model based on fundamentals of radical polymerization and literature known rate parameters for the polymerization of n ‐butyl acrylate is validated against molecular analysis and rheological data. The model is used to predict conversion, molar mass distribution, and branching densities in form of short and long chain branching. Rheological measurements of synthesized model polymers are evaluated along the Carreau‐Yasuda and Van Gurp‐Palmen presentations, allowing to detect small differences in the degree of long chain branching. Contributions of anharmonics to viscoelastic response in large amplitude oscillations are small and differences between the products are dominated by the differences in molar mass. Abstract : A kinetic model for the polymerization of n ‐butyl acrylate is validated against analytical data and used to simulate short‐ and long‐chain branching (LCB) densities for model polymers. With this, small differences in LCB can be interpreted in rheological measurements in the small amplitude oscillation shear (SAOS) and large amplitude oscillation shear (LAOS) region. This enhances the understanding of how polymerization process, branching and polymer (flow) properties are connected.